Comparative Sustainability Assessment of Petroleum Epoxy Resin and Hybrid Bio-based Epoxy Systems Synthesized from Renewable and Waste-Derived Feedstocks - Ghimire, Sachin; Gnawali, Chhabi Lal (Tribhuvan University Journal, 2026)
Convetional epoxy resins derived from diglycidyl ether of bisphenol A (DGEBA) carry a cradle-to-gate carbon footprint of 6.0–8.5 kg CO2-equivalent per kilogram, emit measurable concentrations of volatile organic compounds (VOCs) during application and lack credible end-of-life recovery pathways. These drawbacks conflict increasingly with tightening environmental standards and the construction sector’s transition toward circular material flows. The present study evaluates the sustainability credentials of four epoxy formulations within a single unified framework: a petroleum DGEBA benchmark (Sample P), a binary DGEBA–epoxidised soybean oil (ESO) blend (Sample PE) and two quaternary hybrid bio-based systems, one containing DGEBA, ESO and sugarcane bagasse biochar (Sample B), and a second further supplemented with beeswax (Sample BB). Bio-based carbon content was determined by stoichiometric mass-balance calculation in accordance with ASTM D6866, yielding values of 0%, 9.09%, 10.06%, and 10.46%, respectively. Volatile organic compound content was measured gravimetrically per ASTM D2369 as percent mass loss. Sample Metrics declined systematically from 8.53% (P) to 3.49% (BB), corresponding to a 59% reduction across the formulation series. Similarly, Cradle-to-gate carbon footprints were estimated by process-based allocation following ISO 14044 boundaries, sshowcaing decrease from 10.40 kg CO2eq/kg (P) to 9.30 kg CO2eq/kg (BB). Circular economy performance was expressed through a four-indicator Waste Utilisation Index (WUI) integrating renewable input fraction, waste-stream diversion, avoided fossil carbon and end-of-life valorisation potential. The Sample P yielded WUI = 0, while Sample BB attained WUI = 0.043, driven by the incorporation of waste-derived biochar and apicultural by-products. In the integrated Sustainable Material Index (SMI), which aggregates all four sustainability dimensions by equal-weight min–max normalisation, Sample BB scored 0.9896 against 0.5751 for Sample PE and 0.0000 for Sample P. These findings establish a reproducible multi-metric protocol directly applicable to green procurement decisions in construction and coatings industries.